1997
DOI: 10.1103/physrevd.56.5040
|View full text |Cite
|
Sign up to set email alerts
|

(1+1)-dimensional Yang-Mills theory coupled to adjoint fermions on the light front

Abstract: We consider SU (2) Yang-Mills theory in 1+1 dimensions coupled to massless adjoint fermions. With all fields in the adjoint representation the gauge group is actually SU (2)/Z 2 , which possesses nontrivial topology. In particular, there are two distinct topological sectors and the physical vacuum state has a structure analogous to a θ vacuum. We show how this feature is realized in light-front quantization, with periodicity conditions in x ± used to regulate the infrared and treating the gauge field zero mode… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1997
1997
1999
1999

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…As we saw in the previous subsection supersymmetry leads to the cancellation of the anomaly terms in current operator. However these terms played an important role in the description of Z N degeneracy of vacua [70], so we should find another explanation of this fact here. It appears that fermionic zero modes give a natural framework for such treatment.…”
Section: Supersymmetry and Degenerate Vacuamentioning
confidence: 82%
See 1 more Smart Citation
“…As we saw in the previous subsection supersymmetry leads to the cancellation of the anomaly terms in current operator. However these terms played an important role in the description of Z N degeneracy of vacua [70], so we should find another explanation of this fact here. It appears that fermionic zero modes give a natural framework for such treatment.…”
Section: Supersymmetry and Degenerate Vacuamentioning
confidence: 82%
“…The explicit form of T depends on the rank of the group, for SU(2) and SU(3) it may be found in [59]. The operator S satisfies the condition S N = 1 and it was used in classifying the vacua [59,70].…”
Section: 5)mentioning
confidence: 99%
“…An interpretation of the matrix model for M(atrix) Theory at finite N has also been given by Susskind [9], providing additional motivation to study super Yang-Mills at finite N. We should stress, however, that in the model we study here, we compactify the null direction x − , rather than in a spatial direction. Furthermore, we drop the zero mode sector [14,15], which is conventional in DLCQ, and therefore we eliminate any possibility of connecting our solutions with an equal time quantization of the same theory with a spatially compactified dimension. However, experience with DLCQ has shown that the massive spectrum is insensitive to how the theory is compactified, and to the zero modes.…”
Section: Introductionmentioning
confidence: 99%
“…Schematically, the general structure of an arbitrary Fock state with k traces has the form 14) where n denotes the total number of partons in each Fock state, and the integers i 1 , i 2 , . .…”
mentioning
confidence: 99%